2006
DOI: 10.1017/cbo9780511755071
|View full text |Cite
|
Sign up to set email alerts
|

The Germanic Languages

Abstract: Germanic - one of the largest sub-groups of the Indo-European language family - comprises 37 languages with an estimated 470 million speakers worldwide. This book presents a comparative linguistic survey of the full range of Germanic languages, both ancient and modern, including major world languages such as English and German (West Germanic), the Scandinavian (North Germanic) languages, and the extinct East Germanic languages. Unlike previous studies, it does not take a chronological or a language-by-language… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…In fact, diachronic research into the loss of dative case in Swedish suggests that the rise of the definite article in that language had a temporary conserving effect on the case system (Skrzypek 2005). It is also to be noted that the case distinctions preserved in German are found mainly on determiners, including definite and indefinite articles, while the noun paradigms exhibit little inflection (Harbert 2006). In this sense, the two categories of case and definiteness interact, in that they are encoded together on the same formative (see also Lyons C. 1999:199).…”
Section: Definiteness and Casementioning
confidence: 99%
“…In fact, diachronic research into the loss of dative case in Swedish suggests that the rise of the definite article in that language had a temporary conserving effect on the case system (Skrzypek 2005). It is also to be noted that the case distinctions preserved in German are found mainly on determiners, including definite and indefinite articles, while the noun paradigms exhibit little inflection (Harbert 2006). In this sense, the two categories of case and definiteness interact, in that they are encoded together on the same formative (see also Lyons C. 1999:199).…”
Section: Definiteness and Casementioning
confidence: 99%
“…As König & Auwera (1994: 27, 36) note, the diversity of relative markers in extant Germanic languages suggests that Proto‐Germanic had no single relative marker. Proto‐Germanic is not thought to have used interrogative pronouns as relativizers, instead employing relativization strategies such as nominalization in the form of participial relative constructions (Harbert 2006: 421) or the use of demonstrative pronouns (Harbert 2006: 436). König & Auwera (1994: 68) note that Old Norse, the most direct ancestor to Icelandic, lacks relative pronouns, instead using er , and that sem —which stems from a comparative particle similar in function to English as (Harbert 2006: 426)—replaces er by the fourteenth century.…”
Section: The Role Of Contactmentioning
confidence: 99%
“…It is generally regarded as archaic, poetic, and rather un‐Icelandic, a pattern which exists in the language ‘presumably because of foreign influence’ (Þráinsson 2007: 407). As Proto‐Germanic is not thought to have featured an interrogative–relative pronoun (König & Auwera 1994: 27, 36; Harbert 2006: 437–438), the development of the interrogative–relativization strategy must result from an independent innovation in Icelandic (or earlier in Old Norse) or through language contact. Interrogative–relative polysemy is cross‐linguistically rare outside European languages and even within Indo‐European languages is thought to spread primarily through contact with other Indo‐European languages (Heine & Kuteva 2003: 541; see Section 4.2 for discussion).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, Bybee et al (1994:253) found that "the most frequent [lexical] sources [of future grams] are movement verb constructions." For example, in a number of Germanic languages, future auxiliaries have developed from verbs of motion (see König & Van der Auwera 2002, Harbert 2007). 56 In many cases, a form of go + infinitive or come + infinitive is used to express events taking place in the near future.…”
Section: 3mentioning
confidence: 99%